FAKTOR – FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN NON-CYCLICALS DI BEI - Rafi Zaki Prakoso; F.X. Kurniawan Tjakrawala (Jurnal Paradigma Akuntansi, 2026)
This study aims to determine the effect of leverage, profitability and growth opportunity on cash holdings. The sector used in this study is the consumer non-cyclicals sector (primary consumers) listed on the Indonesia Stock Exchange from 2017 to 2020, the sample selection used a purposive sampling method according to the data that had been selected based on criteria, namely 42 companies. The data processing technique uses multiple regression analysis using SPSS (Statistical Product and Service Solution) 25th edition. The results of this study indicate that leverage has no effect on cash holdings. While Profitability and Growth Opportunity affect cash holdings.